Association between Degree of Anaplasia and Degree of Inflammation with the Expression of COX-2 in Feline Injection Site Sarcomas. (November 2018) - Santelices Iglesias, O.A.; Wright, C.; Duchene, A.G.; Risso, M.A.; Risso, P.; Zanuzzi, C.N.; Nishida, F.; Lavid, A.; Confente, F.; Díaz, M.; Portiansky, E.L.; Gimeno, E.J.; et al.
Summary: Feline injection site sarcomas (FISSs) are mesenchymal neoplasms that develop at the sites of delivery of vaccines or other injectable products. Vaccine adjuvants can trigger an intense and persistent inflammatory response that may lead to neoplastic transformation. The proinflammatory role of cyclo-oxygenase (COX)-2 is well known and its overexpression has prognostic value in multiple neoplastic processes. One hundred and seventeen FISSs were evaluated for the degree of inflammation and anaplasia. Immunohistochemistry was used to determine the expression of COX-2 in these sarcomas. There was a significant association between the degree of inflammation and the expression of COX-2 by neoplastic cells. COX-2 expression was lower in tumours with higher degrees of anaplasia. These findings may be useful in predicting the sensitivity of FISSs to treatment with COX-2 inhibitors. The potential therapeutic use of such agents could then be restricted to tumours with lower degrees of anaplasia. Graphical abstract: